Flotação direta de rejeitos de minério de ferro : avaliação de coletores mistos - Leonardo Júnior Fernandes Campos (2022)
Recent events involving iron ore tailings dam collapses have highlighted the need to seek alternatives for the disposal of this material. This work has as main goal the evaluation of the use of direct flotation for an iron ore tailing from Mariana - MG. The characterization of the sample showed that the material displays low Fe content (10.8% Fe) and a simplified mineralogy, containing only quartz (85%) and hematite (15%). The sample shows a substantial amount of small inclusions of hematite grains in quartz particles, which leads to a reduced degree of liberation for the course granulometric ranges. The use of dodecylamine (DDA) and a reagent based on fatty acids, named AGEM, were evaluated separately and as a mixed collector. The results showed that the mixed collector in the mass ratio DDA:AGEM of 1:5 presented the best results, with 54.06% Fe in the final concentrate, and 32.60% Fe recovery. The better performance of the mixed collector can be explained by the greater stability of the monolayer formed by the reagent, as a result of the reduced electrostatic repulsion between ions of the same species. A granulometric sieving on 150µm in the test feed was analyzed, showing a significant improvement in the test with the mixed collector 1:5, obtaining a final concentrate with 64.06% Fe. A flowsheet change, with the addition of a scavenger stage, was evaluated, although without success. It was also examined the possibility of adopting a magnetic separation step prior to direct flotation, which showed promising results for pre-concentration and also potential for obtaining high purity quartz. Another possibility explored by the study was the use of sodium hexametaphosphate as a depressant, instead of sodium silicate, used in the previous tests. In this case, the result was positive, with an increase in Fe recovery to 35.69%, with a final concentrate with 61.08% Fe. The feasibility of using some hydroxamates and a sulfosuccinamate for the direct flotation, both separately and in the composition of the mixed collector in a 1:5 mass ratio, was also addressed in this study. The results showed that the hydroxamate Aero® 6494 Promoter presented the best performance when used alone in the direct flotation system. However, when exploring the use of these reagents in the constitution of the mixed collector, the hydroxamates did not present satisfactory performance, unlike the sulfosuccinamate Aero® 845 Promoter, which lead to a final concentrate with 62.84% Fe and 59.01% Fe recovery. The mixed collector was evaluated in a pneumatic cell, however, a lower performance was obtained compared to the tests in bench cell, regarding Fe recovery.